Comparison of [3H]-Thymidine, Carboxyfluorescein Diacetate Succinimidyl Ester and Ki-67 in Lymphocyte Proliferation - Lee, Hsin-Ju; Gau, Chun-Chun; Lee, Wan-Fang; Lee, Wen-I; Huang, Jing-Long; Chen, Shih-Hsiang; Yeh, Ho-Yu; Liang, Chi-Jou; Fu, Shih-Hang (Frontiers in Pediatrics, 2022)
Background: Patients with T cell deficiency <10% of normal proliferation are indicated to receive immune reconstruction by hematopoietic stem cell transplantation (HSCT). The aim of this study was to investigate whether non-radioactive assays can be used to quantitatively detect lymphocyte proliferation <10% of normal in addition to radioactive [3H]-thymidine”? Methods: Radioactive [3H]-thymidine, non-radioactive carboxyfluorescein diacetate succinimidyl ester (CFSE) and Ki-67 protein expressions were used to measure lymphocyte proliferation as calculated using the stimulation index (SI), subtraction percentage, and proliferation index (FlowJo software). Normal references were established for comparison in the absence of parallel healthy controls. Results: Normal ranges of mitogen-stimulated lymphocyte proliferation were established as a SI of 15-267 (CSFE 47-92%, Ki-67 42-79%) with PHA 5 ug/mL stimulation; 19-139 (CFSE 62-83%, 45-74% Ki-67) with ConA 5 ug/mL stimulation; 7-53 (CFSE 6-23%, Ki-67 10-24%) with PWM 0.1 ug/mL stimulation; 3-28 (CFSE 4-10%, Ki-67 5-14%) with candida 10 ug/mL stimulation; and 2-27 (CFSE 6-41%, Ki-67 6-30%) with BCG 0.02 ng/mL stimulation. The normalized CFSE-proliferation index was between 2.1 and 3.0. Although there was no significant correlation between these three assays in the healthy controls, the SI value for <10% [3H]-thymidine proliferation in those with T cell deficiency was compatible with CFSE- and Ki-67-stained lymphocyte percentages, and validated in patients with IL2RG, RAG1 and ZAP70 mutations. When calculating [3H]-thymidine <10% of normal lymphocyte proliferation, the threshold of the parallel controls was more reliable than previously established normal references. Conclusion: The large quantitative value of radioactive [3H]-thymidine was more easily recognizable than that for non-radioactive CFSE and Ki-67. Even though the correlation was not significant, those identified to have <10% of normal proliferation by [3H]-thymidine could be consistently detected by CFSE and Ki-67, and consequently indicated for HSCT.